Identifikasi Struktur Bawah Permukaan berdasarkan Analisis Data Gayaberat di Daerah Palembang dan sekitarnya sebagai Cekungan Potensi Hidrokarbon - Eddy Mirnanda; Alfalah Adam Saputra; Lukman Arifin (Department of Physics, Sebelas Maret University, 2023)
Research has been conducted in the Palembang and surroundings areas using gravity data with the aim of knowing the basin structure that has hydrocarbon potential based on 2D and 3D modeling. The Palembang and surroundings areas is one of the regions that has hydrocarbon potential which is characterized by several Sub-Basins namely the South Jambi Sub-Basin, the North Palembang Sub-Basin, and the West Palembang Sub-Basin. The study area has a Complete Bouguer Anomaly value (CBA) between +21 mGal to +55 mGal. Based on 2D modeling, rocks with a density value of around 2.35 gr/cm3 are identified as reservoir zones located in the Talang Akar Formation with depths of around 4000 meters to 5000 meters below the surface. Rocks with density values between 2.35 gr/cm3 to 2.40 gr/cm3 are identified assealsin the form of shale as cover rocks that are good at trapping hydrocarbons. In 2D modeling there are fault structures in the form of normal faults and reverse faults that are identified based on analysis Second Vertical Derivative (SVD). Based on 3D gravity inversion modeling, the reservoirzone was found to be at a depth of about 4000 meters to 5000 meters below the surface which has a density value between 2.31 gr/cm3 to 2.53 gr/cm3.